The Characteristics of Self-assembled Tussah Silk Fibroin Nanoparticles for Controlled Drug Release (Journal of Fiber Bioengineering and Informatics, 2014)
Tussah silk fibroin is a promising material for drug release because of protein component, biocompatibility,aqueous processability, and biodegradability. Tussah silk fibroin nanoparticles were self-assembled andprepared in this paper. Their appearances and sizes were modified by altering the volume ratios betweentussah silk fibroin and ethanol. When 9 mL of ethanol was added, the average microsphere size was184.52 nm and the scattered index was 0.2903. The tussah silk fibroin nanoparticles for controlled drugrelease was studied and the result showed that the time of drug release was significantly longer. Theprocess of drug release was divided into rapid release in early stage and slow release in late stage. Thetarget drug delivery can reduce the negative effects and improve the efficiency of the drug. As a result,it favors deeper investigation of tussah silk fibroin nanoparticles as drug carriers for controlled release ofsensitive biologicals.
Keywords: Tussah Silk Fibroin; Nanoparticle; Drug Release; Self-assembly